Behavioral and Physiological Characterization of PKC-dependent Phosphorylation in the Grin2aΔPKC mouse - Balu, Deebika; Larson, John R.; Schmidt, Jennifer V.; Wirtshafter, David; Yevtodiyenko, Aleksey; Leonard, John P. (Brain research, 2016)
Activity-dependent plasticity in NMDA receptor-containing synapses can be regulated by phosphorylation of serines and tyrosines in the C-terminal domain of the receptor subunits by various kinases. We have previously identified S1291/S1312 as important sites for PKC phosphorylation; while Y1292/Y1312 are the sites indirectly phosphorylated by PKC via Src kinase. In the oocyte expression system, mutation of those Serine sites to Alanine (that cannot be phosphorylated) in the GluN2A subunit, resulted in a decreased PKC stimulated current enhancement through the receptors compared to wild-type NMDA receptors. To investigate the behavioral and physiological significance of those PKC-mediated phosphorylation sites in vivo, the Grin2a Δ PKC mouse expressing GluN2A with four mutated amino acids: S1291A, S1312A, Y1292F and Y1387F was generated using homologous recombination. The Grin2a Δ PKC mice exhibit reduced anxiety in the open field test, light dark emergence test, and elevated plus maze. The mutant mice show reduced alternation in a Y maze spontaneous alternation task and a in a non-reinforced T maze alternation task. Interestingly, when the mutant mice were exposed to novel environments, there was no increase in context-induced Fos levels in hippocampal CA1 and CA3 compared to home-cage Fos levels, while the Fos increased in the WT mice in CA1, CA3 and DG. When the SC-CA1 synapses in slices from mutant mice were stimulated using a theta-burst protocol, there was no impairment in LTP. Overall, these results suggest that at least one of those PKC-mediated phosphorylation sites regulates NMDAR-mediated signaling that modulates anxiety.